Variáveis individuais e estruturais associadas com uma cultura inovadora, o milho no estado do Amazonas - Bara Melgaço, Seima; G Francis, David; de Vasconcelos Barros, Edgard; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
Following the line of thought that development must be approached as a process of structural transformation, the Agricultural Extension Agency in the State of Amazonas: EMATER-AM, conducted the present study to examine the role of agriculture.